2017
DOI: 10.2196/mhealth.7177
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Mobile Apps for Improving Asthma Self-Management: A Review of Publicly Available and Well-Adopted Asthma Apps

Abstract: BackgroundEffective disease self-management lowers asthma’s burden of disease for both individual patients and health care systems. In principle, mobile health (mHealth) apps could enable effective asthma self-management interventions that improve a patient’s quality of life while simultaneously reducing the overall treatment costs for health care systems. However, prior reviews in this field have found that mHealth apps for asthma lack clinical evaluation and are often not based on medical guidelines. Yet, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 26 publications
4
116
0
Order By: Relevance
“…24 To our knowledge, many applications were designed for asthma self-management; however, most of them have not been based on the clinical guidelines and have not been developed with the participation of clinical experts. 26 Therefore, it was suggested that the medical experts to be involved in mobile asthma application projects and the applications should be empirically evidence-based. 27…”
Section: Background and Significancementioning
confidence: 99%
“…24 To our knowledge, many applications were designed for asthma self-management; however, most of them have not been based on the clinical guidelines and have not been developed with the participation of clinical experts. 26 Therefore, it was suggested that the medical experts to be involved in mobile asthma application projects and the applications should be empirically evidence-based. 27…”
Section: Background and Significancementioning
confidence: 99%
“…A study examining the use of mobile technology among individuals with diabetes, for example, found improvements in self-rated wellness scores and several quality-of-care metrics (Bovbjerg et al 2017). Reviews of health care management apps for asthma (Tinschert et al 2017) and bipolar patients (Nicholas et al 2017) showed promise for monitoring symptoms and providing condition-specific information.…”
Section: Use Of Mobile Technology In Health Carementioning
confidence: 99%
“…Reviews of health care management apps for asthma (Tinschert et al . ) and bipolar patients (Nicholas et al . ) showed promise for monitoring symptoms and providing condition‐specific information.…”
Section: Introductionmentioning
confidence: 99%
“…Quinn et al used a smartphone-based software to provide the behavioral therapy of type II diabetes mellitus [14]. Other studies also have proved that the Internet can be successful to promote weight loss [17], increase physical activity [18], and improve self-management behaviors [19].…”
Section: Introductionmentioning
confidence: 99%